2015
DOI: 10.17533/udea.rccp.v28n2a06
|View full text |Cite
|
Sign up to set email alerts
|

Presence of paratuberculosis in dairy cows culled in Tizayuca (Hidalgo, Mexico)

Abstract: Presence of paratuberculosis in dairy cows culled in Tizayuca SummaryBackground: paratuberculosis (PTB) is clinically characterized by diarrhea and progressive weight loss in ruminants, and causes economic losses due to decreased milk production, premature animal disposal, and increased veterinary treatment costs. The presence of PTB has been increasing in milk producing bovine farms in Mexico, yet epidemiology data from specific farms remains scarce. Objective: to determine the proportion of cows positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…Based on gross post mortem examination of tissue samples in the present abattoir study, the prevalence of gross lesions resembling paratuberculosis recorded in the present study was in line with the results reported by the study conducted earlier [27]. However, the prevalence of gross lesions resembling paratuberculosis found in this study is lower than those reported previously in other countries [5, 14], while it was higher than nding reported by other authors [28,29]. The difference in the prevalence of paratuberculosis gross lesions could be due to the difference in the origin or type of production system, age of the host, immune status and breed of the animals that are slaughtered in the abattoir.…”
Section: Discussionsupporting
confidence: 92%
“…Based on gross post mortem examination of tissue samples in the present abattoir study, the prevalence of gross lesions resembling paratuberculosis recorded in the present study was in line with the results reported by the study conducted earlier [27]. However, the prevalence of gross lesions resembling paratuberculosis found in this study is lower than those reported previously in other countries [5, 14], while it was higher than nding reported by other authors [28,29]. The difference in the prevalence of paratuberculosis gross lesions could be due to the difference in the origin or type of production system, age of the host, immune status and breed of the animals that are slaughtered in the abattoir.…”
Section: Discussionsupporting
confidence: 92%
“…Genotype typification studies have detected Type C and its different subtypes in both red deer (Cervus elaphus) and scimitar-horned oryx [16,32]. These results agree with those in reports from Mexico, where Type C MAP has been detected in domestic bovine and caprine populations [20,23,33]. However, it is necessary to perform more extensive studies to understand the genetic diversity of MAP present in wild ruminants under human care in zoological collections, as well as in domestic ruminants in Mexico.…”
Section: Discussionsupporting
confidence: 88%
“…The P3N (5´GGGTGTGGCGTTTTCCTTCG 3´) and P5N (5´ATTTCGCCGCCACCGCCACG 3´) primers were used. These amplify a fragment of 314 bp from the IS900 insertion sequence of MAP [22,23]. For this test, 3 µL of DNA were used (equivalent to 0.5 µg), 20 µL of FastStart™ PCR Master (Roche ® , USA), and 1 µL of each primer.…”
Section: Is900 Pcrmentioning
confidence: 99%